P0 protein of cotton leafroll dwarf virus-atypical isolate is a weak RNA silencing suppressor and the avirulence determinant that breaks the cotton Cbd gene-based resistance - Agrofoglio, Yamila Carla; Delfosse, Veronica Cecilia; Casse, Maria Florencia; Hopp, Horacio Esteban; Bonacic Kresic, Iván; Ziegler-Graff, Véronique; Distefano, Ana Julia (Wiley, 2019)
Cotton blue disease (CBD) is the most important disease present in cotton crops in South America and cotton leafroll dwarf virus (CLRDV) is the causal agent. The disease has been controlled by sowing cotton varieties resistant to CLRDV. However, in the 2009/10 growing season, an outbreak due to an atypical CLRDV isolate (CLRDV‐at) occurred in northwest Argentina. Although CLRDV and CLRDV‐at genomes are very closely related, the symptoms they produce in cotton plants are quite different. P0 is the most divergent protein between the isolates and in CLRDV is a silencing suppressor protein. This work characterized the silencing suppressor activity of the P0 protein encoded by CLRDV‐at (P0CL‐at) and evaluated its role in Cbd‐resistance break in cotton plants. It was demonstrated that P0CL‐at, despite having a mutation in the consensus of the F‐box‐like motif, was able to suppress local RNA silencing, but displayed lower activity than P0CL. P0CL and P0CL‐at showed no differences in the interaction with Gossypium hirsutum SKP1 orthologue (GSK1) and Nicotiana benthamiana SKP1 and both P0 proteins triggered destabilization of ARGONAUTE1. However, when the ability to enhance PVX symptoms was evaluated, P0CL‐at was shown to be a weaker pathogenicity factor than P0CL in N. benthamiana. Interestingly, trans‐expressed P0CL‐at enabled CLRDV to systemically infect CBD‐resistant plants, and a chimeric CLRDV‐P0CL‐at infectious clone succeeded in establishing infection in CBD‐resistant cotton varieties with symptoms resembling those produced by CLRDV‐at. These results strongly suggest that P0CL‐at is the avirulence (Avr) determinant involved in breaking cotton Cbd gene‐based resistance.